Nutrient sensing pathways as therapeutic targets for healthy ageing. (3rd April 2017) - Aiello, Anna; Accardi, Giulia; Candore, Giuseppina; Gambino, Caterina Maria; Mirisola, Mario; Taormina, Giusi; Virruso, Claudia; Caruso, Calogero
ABSTRACT: Introduction : In the present paper, the authors have discussed anti-aging strategies which aim to slow the aging process and to delay the onset of age-related diseases, focusing on nutrient sensing pathways (NSPs) as therapeutic targets. Indeed, several studies have already demonstrated that both in animal models and humans, dietary interventions might have a positive impact on the aging process through the modulation of these pathways. Areas covered : Achieving healthy aging is the main challenge of the twenty-first century because lifespan is increasing, but not in tandem with good health. The authors have illustrated different approaches that can act on NSPs, modulating the rate of the aging process. Expert opinion : Humanity's lasting dream is to reverse or, at least, postpone aging. In recent years, increasing attention has been devoted to anti-aging therapies. The subject is very popular among the general public, whose imagination runs wild with all the possible tools to delay aging and to gain immortality. Some approaches discussed in the present review should be able to substantially slow down the aging process, extending our productive, youthful lives, without frailty.